Isotherms and thermodynamic properties of water adsorption in ‘Cumari-do-Pará’ pepper seeds - Karen C. Rodrigues; Hellismar W. da Silva; Isneider L. Silva; Samuel G. F. dos Santos; Daniel P. da Silva; Renato S. Rodovalho (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT Studies related to water sorption in seeds are essential for the design and optimization of storage systems. The objective of this research was to determine and model the adsorption isotherms and calculate the latent heat of water vaporization, differential enthalpy and entropy, the isokinetic theory and Gibbs free energy for ‘Cumari-do-Pará’ pepper seeds. The equilibrium moisture contents were obtained by the static gravimetric method at temperatures of 30, 35 and 40 °C and water activities between 0.290 and 0.900 (decimal). The Chen-Clayton model is the one that best represents the water adsorption isotherms in ‘Cumari-do-Pará’ pepper seeds under the studied conditions, with 9.94% mean relative error, 0.40 mean estimated error and random distribution of residuals. The latent heat of vaporization ranged from 2,555.669 to 3,162.180 kJ kg-1. The enthalpy, entropy and Gibbs free energy increase with the reduction in the equilibrium moisture content of the seeds. The isokinetic theory is valid for the adsorption process.